Do valve type and post-ballooning affect transprosthetic gradients in patients undergoing transcatheter aortic valve-in-valve procedure?. (3rd October 2022) - Fusini, L; Muratori, M; Tamborini, G; Gripari, P; Ghulam Ali, S; Cefalu', C; Fabbiocchi, F; Galli, S; Roberto, M; Agrifoglio, M; Pontone, G; Bartorelli, A L; et al.
Abstract: Introduction: Valve-in-Valve transcatheter aortic valve implantation (ViV-TAVI) is an appealing treatment option for patients with degenerated aortic bioprosthetic valves. However, high post-procedural transprosthetic gradients are very common after ViV-TAVI than after TAVI for native-valve aortic stenosis. Aim: We sought to evaluate transprosthetic gradients (ΔP) and hemodynamic outcome in patients undergoing ViV-TAVI according to valve type and balloon post-dilation (balloon-expandable vs self-expandable with and without post-dilation). Material and methods: We retrospectively analyzed 111 patients undergoing ViV-TAVI. A balloon-expandable valve was used in 35 patients (32%, Group 1), a self-expandable valve in 76 cases of which 39 (35%, Group 2) without balloon post-dilation and 37 (33%, Group 3) with balloon post-dilation. A comprehensive transthoracic echocardiography (TTE) was performed in all patients at baseline, at discharge and at 6-months follow-up. Results: Successful ViV-TAVI was performed in 110 patients (99%). Baseline peak and mean ΔP, left ventricular volumes, ejection fraction, and pulmonary artery systolic pressure were similar among groups. A significant improvement in all echocardiographic parameters was observed in all groups over time (Table 1). In particular, a significant reduction in postprocedural gradients was observed at discharge and at 6-months follow-up compared to baseline in all groups. Immediately after ViV-TAVI procedure, the lowest value of mean ΔP was observed in Group 3 (12±7 mmHg) compared to both Group 1 (20±9 mmHg) and Group 2 (17±8 mmHg, p=0.001). This result was confirmed at 6-months follow-up (p=0.012). Rate of small valve size (≤23 mm) implanted was similar among groups (Group 1: 78%, Group 2: 60%, Group 3: 62%, p=0.123). Similar 1-year all-cause mortality was observed among groups (9%, 13%, 0%, respectively, p=0.135). Conclusions: In patients with failed surgical aortic prosthesis, ViV-TAVI is an effective option and is associated with sustained improved hemodynamics in all patients. Anyway, the choice of prosthetic valve type and implantation technique are relevant on residual transprosthetic gradients and should be taken into account for a better long-term outcome. Funding Acknowledgement: Type of funding sources: None.